RESEARCH ON THE IMPACT OF GOVERNMENT, INDUSTRY AND ACADEMIA ON THE CULTIVATION OF “CHINESE + VOCATIONAL SKILLS” TALENTS UNDER THE BACKGROUND OF CHINA-LAOS VOCATIONAL EDUCATION COOPERATION - Zheng Shen (Fonseca, Journal of Communication, 2024)
Based on the triple helix theory, a theoretical model of the China-Laos government-industryacademic participation, teachers’ teaching and industry-university-research capabilities, international students’ subjective initiative and the impact of “Chinese + vocational skills” talent training was constructed, and the teacher-student correlation was proposed Ability is hypothesized as a mediating variable and tested through structural equation modeling. the theoretical discussion and empirical research of the paper deepens the research on “Chinese + vocational skills” talent training.